Experimental and numerical studies on thermal behavior and performance assessment of Al2O3/H2O nanofluids in microchannels for cooling solutions - An-Shik Yang; Yen-Ren Liao; Zhengtong Li; Chih-Yung Wen; Yee-Ting Lee (International Journal of Thermofluids)
Nanofluids in microchannels have been a promising possibility for electronic cooling uses due to high heat removal rates and reduced energy consumption. This study conducts the experimental measurements to analyze the combined effects of concentration of nanoparticles and geometrical design in terms of the aspect ratio (AR) and hydraulic diameter (Dh) on the thermal and frictional outcomes of Al2O3/water nanofluids throughout the microchannels at varied Reynolds numbers and heat loads. Theoretically, the computational fluid dynamics (CFD) simulations are performed using the three-dimensional (3D) single-phase and mixture models to determine the velocity, temperature and nanoparticle concentration distributions. The predicted heat transfer coefficients and pressure drops using the mixture model agree well with the experimental data for model validation. In the impact study, an increase in AR from 2.0 to 5.0 can increase the average pressure drop and heat transfer coefficient by 28.2 %-41.5 % and 23.9 %-38.3 % over the Reynolds numbers of 300–1900, respectively. In contrast, the decline of Dh from 1.38 mm to 0.92 mm can intensify flow resistance and heat transfer by 24.4 %-35.5 % and 21.3 %-36.6 %. Among the assessments of four well-known correlations, the related correlation from Chen and Cheng achieves the most accurate estimates of the Nusselt number of Al2O3/water nanofluid. The microchannel layout with an aspect ratio of 5.0 can achieve the thermal performance factor up to 1.17.